Perancangan UI/UX Aplikasi Perpustakaan Digital Berbasis Web Menggunakan Metode Design Thinking - Nico Saputra; Satria Dimaz Mahendra; Sherafli Rusli (MDP Student Conference, 2026)
The rapid development of information technology has driven the transformation of library services from conventional systems to web-based digital libraries. However, many digital library applications still experience issues related to user interface and user experience, particularly in ineffective and unintuitive book search features. This study aims to design the UI/UX of a web-based digital library application using the Design Thinking method with a focus on book searching. The Design Thinking method consists of five stages: empathize, define, ideate, prototype, and test. The empathize stage identifies user needs and problems in searching for books. The define stage formulates the main problems, while the ideate stage generates user-centered design solutions. The prototype stage produces interface designs, and the test stage evaluates usability and user comfort. The results show that the proposed UI/UX design improves the effectiveness of book searching and enhances user experience. This study is expected to serve as a reference for developing user-centered web-based digital library applications.